EMERGENCE OF LINEZOLID RESISTANCE IN COAGULASE-NEGATIVE STAPHYLOCOCCUS ISOLATED FROM A POST-SURGICAL CASE OF CORONARY ARTERY BYPASS AT A TERTIARY CARE CARDIAC SETUP IN PAKISTAN - Afzal, Raja Kamran; Nida, Sumbal; Saeed, Mohammed Zaheer Us; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2018)
Linezolid is first choice in the treatment of methicillin resistant Staphylococci. Resistance to this antibiotic is quite rare. We report the first case of linezolid resistant coagulase negative Staphylococcus from a tertiary care cardiac setup in Pakistan. The strain was isolated from pus swab of a 62 year old female from post-coronary bypass grafting sites.